Motor Matt's Peril; or, Cast Away in the Bahamas : Motor Stories Thrilling Adventure Motor Fiction No. 12, May 15, 1909 - Matthews, Stanley R. (Salt Lake City, UT : Project Gutenberg, 2015)
"Motor Matt's Peril; or, Cast Away in the Bahamas" by Stanley R. Matthews is an adventure novel written in the early 20th century. The story centers around the daring escapades of Matt King, a skilled young motorist known for his athletic abilities, along with his friends Carl Pretzel and Dick Ferral. They embark on a journey that takes them from Atlantic City to the Bahamas, facing challenges and intrigue related to a stolen submarine and a mysterious treasure." "The beginning of the story introduces the characters on a beach in Atlantic City, where Carl Pretzel humorously attempts to rescue a girl from what he perceives to be pirates, inadvertently interrupting a film shoot. This leads to a series of comedic realizations and encounters, including the arrival of Motor Matt, who joins Carl in the fray. The unfolding drama sets the stage for a deeper plot involving the theft of a submarine, the pursuit of treasure purportedly hidden on a Bahamian island, and the boys' determination to right the wrongs that ensue. As they prepare for an aerial adventure, intriguing twists already hint at the perils they will face ahead." (This is an automatically generated summary.)
Release date is 2015-03-03
E-text prepared by David Edwards, Demian Katz, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Villanova University Digital Library (http://digital.library.villanova.edu/)
Keywords: Adventure stories; Submarines (Ships) -- Juvenile fiction; Airships -- Juvenile fiction; Castaways -- Juvenile fiction; Dime novels; Mechanics -- Juvenile fiction; Bahamas -- Juvenile fiction